Sound design & science fiction - Whittington, William (Austin, TX : University of Texas Press, 2007)
pt. I. The dawn of sound design ## pt. II. Sound Montage ## pt. III. Sound designing ## pt. IV. Sound effects ## pt. V. Voice design ## pt. VI. Final design ## pt. VII. A sounding of the future.
boek